Waking the dead: Civilian casualties in the Namibian liberation struggle (Journal for Studies in Humanities and Social Sciences, 2014)
The liberation Struggle is marked by an absence of archival sources. This absence leads to an impossibility of systematic historical analysis of conflicting archival evidence; as a result, history is created with a broad brush on a monumental landscape. In terms of public history, the emphasis has been placed on the memory of the soldiers who died fighting in the liberation struggle. A post-war publication has listed their names, although those who died on Namibian soil remain buried in anonymous graves. The internet provides a virtual graveyard, which attempts to unite all those who died on the South African side during their "Border War'. Such lists suggest that the compilers have been able to enter inaccessible archives and/or contact knowledgeable informants. Yet many of the soldiers who died, on both sides, during the Namibian liberation Struggle died in Southern Angola and the community memory of the war in Namibia is more closely linked to the many incidents in which civilians were killed inside Namibia during the conflict. In Namibia, almost a generation after the end of the war, it remains unknown how many Namibian civilians died during the Namibian Liberation Struggle. Where estimates are provided, the victims are reduced to nameless numbers. The absence of a consolidated archival record of these deaths means that an important dimension of the war remains hidden. This article will present the work that has been done to create an archive of Civilian Casualties of the Namibian liberation Struggle and discuss some of the challenges and difficulties associated with the project. It will argue that combining a range of sources into a new collection of consolidated information on individual deaths can challenge one of the archival absences on the liberation struggle and shape the historiography of the Namibian liberation struggle that is being created by a new generation of Namibian historians.